1994
DOI: 10.1152/ajprenal.1994.267.4.f639
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and immunocytochemical evidence for a putative H-K-ATPase in elasmobranch renal acid secretion

Abstract: The mechanism of renal acid secretion in marine fish is largely unknown. We explored whether H(+)-K(+)-adenosinetriphosphatase (H(+)-K(+)-ATPase) is present and functional in acid secretion in the kidney of the elasmobranch spiny dogfish shark, Squalus acanthias. In whole animal studies, a specific inhibitor of mammalian H(+)-K(+)-ATPase, Sch-28080, abolished greater than 87% of basal (62 mg/kg) and 75% of imidazole-stimulated titratable acid excretion (5 and 62 mg/kg). Antibodies directed against the COOH-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The acidification in the proximal tubule was also found in the little skate (23). In spiny dogfish, infusion of an inhibitor for mammalian gastric H ϩ -K ϩ -ATPase Sch28080 abolished over 80% of basal acid excretion, implying that H ϩ -K ϩ -ATPasedependent mechanism(s) for urine acidification exist in the elasmobranch kidney (108). These authors conducted immunohistochemistry using an antibody directed against the COOH-terminus of porcine gastric H ϩ -K ϩ -ATPase ␣-subunit and found that the apical and basolateral membranes of many nephron segments were stained with the antibody.…”
Section: Urea Synthesis In the Kidneymentioning
confidence: 89%
“…The acidification in the proximal tubule was also found in the little skate (23). In spiny dogfish, infusion of an inhibitor for mammalian gastric H ϩ -K ϩ -ATPase Sch28080 abolished over 80% of basal acid excretion, implying that H ϩ -K ϩ -ATPasedependent mechanism(s) for urine acidification exist in the elasmobranch kidney (108). These authors conducted immunohistochemistry using an antibody directed against the COOH-terminus of porcine gastric H ϩ -K ϩ -ATPase ␣-subunit and found that the apical and basolateral membranes of many nephron segments were stained with the antibody.…”
Section: Urea Synthesis In the Kidneymentioning
confidence: 89%
“…In the light of these observations and additional in situ measurements of renal acidification in the marine skate Raja erinacea, a novel mechanism of HCO 3 -reabsorption was proposed for elasmobranchs involving (Deetjen and Maren, 1974). Years later, Swenson and colleagues (Swenson et al, 1994) proposed a mechanism for CA-independent urinary acidification involving the secretion of H + via a luminal H + ,K + -ATPase. Although these findings led to, or supported, acceptance of the hypothesis that marine fish lack renal CA, this conclusion is no longer believed given the physiological evidence for cytosolic CA activity in proximal tubules of winter flounder (Renfro et al, 1999;Pelis et al, 2003;Pelis and Renfro, 2004) and the finding of membrane-associated CA IV mRNA in dogfish kidney (Gilmour et al, 2007a).…”
Section: Role Of the Kidney In Acid-base Regulationmentioning
confidence: 99%
“…Meanwhile, molecular anatomy can determine the localization of transport proteins for urea, ions and water in situ, and thus is a powerful tool to overcome the difficulty in studying the elasmobranch kidney. Spatial patterns in the distribution of various pumps (Hentschel et al, 1993;Swenson et al, 1994), channels and transporters (Biemesderfer et al, 1996) in the nephron segments can provide valuable information on the movement of the above molecules across the kidney tubules, and thus on the reabsorption mechanism of urea.…”
mentioning
confidence: 99%